Examining the level of Empathy of second-year Bachelors of Social Work Students at a South African University making use of the Empathy Assessment Index - Louw, Alexander (Department of Social Development, 2019)
The aim of this study was to examine the level of empathy of second-year Bachelors of Social Work (BSW) students using the Empathy Assessment Index (EAI), and the findings were contextualised within the South African social work training policies. The Social Work Model of Empathy and the social cognitive neuroscientific definition of empathy the EAI was built on, forms the guiding theoretical frame for this study. It is often assumed that social work students have adequate levels of empathy and this research study was a first step in determining if this was correct. This has contributed to the discussion on social work education, specifically if more direct instruction or policy changes may be necessary concerning empathy in social work training. The researcher utilised a quantitative research methodology in conjunction with the Empathy Assessment Index in order to collect the data. Univariate descriptive data analysis was used in order to illustrate the findings in a logical and understandable format. The research was conducted using second-year BSW students (n=40) from a Western Cape University and the study found that the respondents had an overall high level of empathy. However, the component score for Emotional Regulation was fairly low. This, according to the literature, could prevent a person from accessing the full benefits of an empathic experience. It was recommended that universities consider implementing more direct methods to train and increase empathic ability. Furthermore, considering how new the study of empathy is to social work in South Africa, it was also recommended that further studies are required for better implementation of the construct, especially to determine what an optimal level of empathy is for a social work student